AB0446 Treatment Effects and Minimal Clinically Important Differences in Patient-Reported Outcomes Following Treatment and Withdrawal of Abatacept, Methotrexate Or Combination Therapy in Patients with Early Rheumatoid Arthritis. (9th June 2015) - Furst, D.E.; Bykerk, V.P.; Burmester, G.R.; Combe, B.G.; Huizinga, T.W.J.; Alemao, E.; Wong, D.A.; Emery, P.
Abstract : Background: Early biologic use can improve long-term control of RA. 1, 2 Minimal clinically important differences (MCIDs) in patient (pt)-reported outcomes (PROs) that are of particular importance to pts with RA, such as pain, fatigue and physical function, can provide benchmarks for intervention. In the AVERT (Assessing Very Early Rheumatoid arthritis Treatment) trial, more anti-cyclic citrullinated peptide 2 seropositive (CCP2+) pts with early RA achieved DAS28 (CRP) <2.6 after 12 months (mths) of treatment with SC abatacept (ABA) + MTX and 6 mths after rapid withdrawal of all RA therapy, compared with MTX alone. 3 Objectives: To investigate the overall treatment effect on PROs and the percentage (%) of pts achieving MCIDs during treatment (baseline to Mth 12) and up to 6 mths after treatment withdrawal in pts who participated in AVERT. Methods: Pts were MTX naïve, anti-CCP2+, ≥18 years old, with active synovitis, DAS28 (CRP) ≥3.2, disease onset of ≤2 years. Pts were randomized to weekly ABA (125 mg) + MTX, ABA (125 mg) or MTX. All RA treatments (biologic agent, MTX and steroids) were withdrawn after 12 mths in pts with DAS28 (CRP) <3.2. In this post hoc analysis, overall treatment effect and treatment differences between ABA + MTX or ABA versus MTX were obtained using a longitudinal repeated-measures model including fixed categorical effects of treatment, visit mth and prior corticosteroid use as well as the continuous fixed covariate of baseline value. The % of pts achieving MCIDs was analysed. Results: A total of 351 pts were enrolled (119 ABA + MTX, 116 ABA, 116 MTX). ABA + MTX had statistically significant effects on fatigue and SF-36 physical component summary (PCS) score versus MTX alone during the treatment period (Table ). Numerically greater percentages of pts being treated with ABA + MTX achieved MCIDs than ABA or MTX alone (Table). In all groups, treatment withdrawal provided continued benefits but at reduced magnitude. Conclusions: Clinically meaningful improvements and significant benefits were seen in physical function and fatigue over 12 mths in an anti-CCP2+, early RA cohort treated with abatacept + MTX. Continued beneficial effects were observed at the group level up to 6 mths even after all RA drugs were withdrawn. References: Westhovens R et al. Ann Rheum Dis 2009;68:1870–7. Emery P et al. Ann Rheum Dis 2010;69:510–6. Emery P et al. Ann Rheum Dis 2014;73(Suppl 2):69. Disclosure of Interest: D. E. Furst Grant/research support from: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Cytori, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: (CME ONLY) AbbVie, Actelion, UCB, V. P. Bykerk Grant/research support from: Amgen, Pfizer, Bristol-Myers Squibb, Janssen, UCB, Roche/Genentech, Consultant for: Amgen, Pfizer, Bristol-Myers Squibb, UCB, Roche, G. R. Burmester Grant/research support from: Bristol-Myers Squibb, AbbVie, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: Bristol-Myers Squibb, AbbVie, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: Bristol-Myers Squibb, AbbVie, Pfizer, MSD, Roche, UCB, B. G. Combe Grant/research support from: Pfizer, Roche-Chugai, Speakers bureau: Bristol-Myers Squibb, Merck, Pfizer, Roche-Chugai, UCB, T. W. J. Huizinga Grant/research support from: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Bioscience, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Meteor Board, Speakers bureau: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. A. Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis